Electrochemical Exfoliation to Produce High-Quality Black Phosphorus - Hashemi, Payam; Sabaghi, Davood; Yang, Sheng; Nia, Ali Shaygan; Feng, Xinliang (Journal of Visualized Experiments, 2022)
To obtain high-quality two-dimensional (2D) materials from the bulky crystals, delamination under an externally controlled stimulus is crucial. Electrochemical exfoliation of layered materials requires simple instrumentation yet offers high-quality exfoliated 2D materials with high yields and features straightforward upscalability; therefore, it represents a key technology for advancing fundamental studies and industrial applications. Moreover, the solution processability of functionalized 2D materials enables the fabrication of (opto)electronic and energy devices via different printing technologies such as inkjet printing and 3D printing. This paper presents the electrochemical exfoliation protocol for the synthesis of black phosphorus (BP), one of the most promising emerging 2D materials, from its bulk crystals in a step-by-step manner, namely, cathodic electrochemical exfoliation of BP in the presence of N(C4H9)4∙HSO4 in propylene carbonate, dispersion preparation by sonication and subsequent centrifugation for the separation of flakes, and morphological characterization by scanning electron microscopy (SEM), atomic force microscopy (AFM), and transmission electron microscopy (TEM).
CRIS-Team Scopus Importer:2023-03-20